Automatic Identification and New Observations of Ion Energy Dispersion Events in the Cusp Ionosphere. Issue 4 (23rd April 2022) - da Silva, D.; Chen, L. J.; Fuselier, S.; Wang, S.; Elkington, S.; Dorelli, J.; Burkholder, B.; Sibeck, D.
Abstract: In this paper we present an algorithm which identifies ion energy dispersion events in low altitude cusp observations. Such an algorithm is suitable for implementation to prioritize data for downlink, or to be run on the ground for data mining. The energy dispersion events, sometimes known as dispersed particle precipitation, have been interpreted as due to time‐of‐flight effects of energized ions from magnetopause reconnection sites. Our algorithm utilizes a novel method of integrating a scoring function across moving time windows to capture the dispersion structure. The algorithm is implemented and prototyped with Defense Meteorological Satellite Program data but specified in terms that apply to other missions for both ions and electrons. Two new types of dispersion events are uncovered with the algorithm, consisting of a cold inverse double dispersion event where one population dominates, and a V‐type dispersion event during northward interplanetary magnetic field. Plain Language Summary: Ion energy dispersion events occur in the low altitude cusp region, originating from reconnection at the magnetopause. This paper presents an algorithm for automatically detecting these events in data from the Defense Meteorological Satellite Program (DMSP) satellites. Though the algorithm is demonstrated with DMSP, the algorithm can work with other satellites. The algorithm is also used to search for new types of dispersion, and two new types of dispersion events are presented in this paper. Key Points: A novel method for capturing the energy dispersion structure is developed and applied to the DMSP data The algorithm is applied and validated against a G2‐class Moderate Storm New types of ion dispersion events are uncovered with the algorithm and their relevance is stated